2014
DOI: 10.1371/journal.pone.0106818
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Profiling of Spinal Muscular Atrophy Motor Neurons Derived from Mouse Embryonic Stem Cells

Abstract: Proximal spinal muscular atrophy (SMA) is an early onset, autosomal recessive motor neuron disease caused by loss of or mutation in SMN1 (survival motor neuron 1). Despite understanding the genetic basis underlying this disease, it is still not known why motor neurons (MNs) are selectively affected by the loss of the ubiquitously expressed SMN protein. Using a mouse embryonic stem cell (mESC) model for severe SMA, the RNA transcript profiles (transcriptomes) between control and severe SMA (SMN2+/+;mSmn−/−) mES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 102 publications
4
39
0
Order By: Relevance
“…Of this group, only Igfbp2 was significantly changed (~1.7-fold increase in skip versus therapeutic ASO-treated mice). This discordance between gene expression and protein changes has been observed in other models of SMN [21]. Notably, although gemin 2 and gemin 8 were not altered at the level of gene expression, the protein levels of both significantly increased with therapeutic ASO treatment, consistent with the observation that SMN stabilizes gemin proteins [3].…”
Section: Induced Transcriptional Changes Can Be Prevented or Reversedsupporting
confidence: 82%
See 2 more Smart Citations
“…Of this group, only Igfbp2 was significantly changed (~1.7-fold increase in skip versus therapeutic ASO-treated mice). This discordance between gene expression and protein changes has been observed in other models of SMN [21]. Notably, although gemin 2 and gemin 8 were not altered at the level of gene expression, the protein levels of both significantly increased with therapeutic ASO treatment, consistent with the observation that SMN stabilizes gemin proteins [3].…”
Section: Induced Transcriptional Changes Can Be Prevented or Reversedsupporting
confidence: 82%
“…Whether gems or the closely associated Cajal bodies couple their roles in splicing and transcription with the DNA damage response is unknown. Although we cannot rule out the contribution of reactive glial proliferation to cell cycle expression changes in the SMA model, a recent study showed that purified motor neuron precursors derived from mouse SMA embryonic stem cells (ESCs) also show marked up-regulation of cell proliferation genes or proteins, including p21, encoded by Cdkn1a [21]. Curiously, p21 levels are up-regulated over 40-fold in SMA mESCs compared to control mESCs, whereas Cdkn1a mRNA levels are down-regulated 0.76-fold [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, low levels of SMN have been linked to widespread changes in expression patterns, [121][122][123][124][125][126][127][128] but it is currently an open question as to how these changes might be linked to Cajal bodies. In addition, the mechanism by which these conformational changes in the nucleus affect the rest of the cell and which cellular components and processes are most severely affected has yet to be studied.…”
Section: Smn and Cajal Body Structurementioning
confidence: 99%
“…However, homologs of NALCN are expressed in the neuromuscular junction in D. melanogaster 18 as well as in motor neurons in C. elegans 19 and mice. 20,21 Accordingly, mutations in NALCN might cause congenital contractures by disturbing motor control of myofiber function during development, similar to the hypothesized effects of mutations in ECEL1, PIEZO2, and CHRNG (MIM 100730).…”
mentioning
confidence: 91%